Influence of CBR Variations on Rigid Pavement Structural Design for Airport Service Roads - I Putu Chandra Wibawa; I Made Agus Ariawan; Made Dodiek Ardana (Interdisciplinary Social Studies, 2025)
Rigid pavement on airport service roads is essential for smooth vehicle operations, with subgrade conditions being the primary factor in determining concrete slab thickness. Variations in the California Bearing Ratio (CBR) of the subgrade commonly affect pavement thickness and construction costs. This study analyzes how changes in subgrade CBR impact rigid pavement thickness for service roads using the empirical method of Pd T-14-2003. It also compares the results with international standards, including FAA AC 150/5320-6G and ICAO Annex 14, to validate findings and assess the relevance of Indonesian standards globally. The research involved collecting traffic data and geotechnical parameters and calculating design thickness variations based on CBR values. Results indicate that each 1% increase in CBR decreases the required concrete slab thickness by 4 mm: 163 mm at 6% CBR, 158 mm at 7%, and 155 mm at 8%. Comparison with international standards shows that Pd T-14-2003 tends to produce conservative designs. However, integrating mechanistic-empirical approaches could improve safety and economic efficiency. These findings demonstrate that enhancing subgrade quality can reduce slab thickness, leading to material savings and lower construction costs. This study advances the traditional CBR approach by incorporating advanced soil mechanics principles and offers a framework for adopting international best practices in Indonesian airport pavement design, supporting the advancement of domestic aviation infrastructure.